(untitled) (Research, Society and Development, 2020)
Introduction: Fibrous dysplasia is a benign fibro-osseous lesion of unknown etiology, characterized by the development of fibrous tissue that gradually replaces normal bone. The pathology can appear in two ways: monostotic, when it involves only one bone; and polyostotic, affecting multiple bones. Malignant transformation of fibrous dysplasia is rare, occurring in less than 1% of cases of the disease and has already been described in both forms of the injury. Objective: The present study aims to present a rare clinical case of craniofacial poliostotic fibrous dysplasia that evolved with malignancy in a 53-year-old woman. Case report: The patient presented with a fast and progressive hemifacial tumor, painful symptoms and imaging findings with a "ground-glass" characteristic, aspects suggestive of malignancy. A biopsy was performed using the Core Biopsy method, which confirmed, through the immunohistochemistry test, the differentiation in intermediate grade fusocellular sarcoma. The patient died after three months from the start of treatment due to gastrostomy complications. Final considerations: Although rare, malignant changes associated with fibrous dysplasia have a poor prognosis. Therefore, the maxillofacial surgeon must be attentive to the signs of malignancy to initiate the appropriate treatment.